2015
DOI: 10.1007/s10404-015-1649-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion on molecular tagging velocimetry technique for rarefied gas flow analysis

Abstract: The molecular tagging velocimetry (MTV) is a well-suited technique for velocity field measurement in gas flows. Typically, a line is tagged by a laser beam within the gas flow seeded with light emitting acetone molecules. Positions of the luminescent molecules are then observed at successive times and the velocity field is deduced from the analysis of the tagged line displacement and deformation. However, the displacement evolution is expected to be affected by molecular diffusion, when the gas is rarefied. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…(1). The first step of the reconstruction method consists in approximating the velocity profile () The application of this reconstruction method to DSMC simulations [62] has shown a very accurate velocity reconstruction from displacements, for Knudsen numbers lower than 0.05, i.e. within the continuum and slip flow regimes.…”
Section: Molecular Diffusion Modeling and Velocity Reconstruction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1). The first step of the reconstruction method consists in approximating the velocity profile () The application of this reconstruction method to DSMC simulations [62] has shown a very accurate velocity reconstruction from displacements, for Knudsen numbers lower than 0.05, i.e. within the continuum and slip flow regimes.…”
Section: Molecular Diffusion Modeling and Velocity Reconstruction Methodsmentioning
confidence: 99%
“…Although diffusion is much less significant in liquids, the authors showed that the velocity close to the walls could be overestimated due to the combination of molecular diffusion and shear stress. They demonstrated that this error, limited to a near wall region of a few micrometers thick, could be Regarding Taylor dispersion in gas microflows, a Direct Simulation Monte Carlo (DSMC) study, led by Frezzotti et al, showed that even in the continuum regime, the tagged molecules are subject to significant molecular diffusion [62]. In case of slip flow, the mechanism illustrated in Fig.…”
mentioning
confidence: 99%
“…In step (d), MTV images are passed through a proper noise filter to make the fitting procedure of step (e) more robust. Finally, step (f) consists in the actual measurement of the velocity profile by means of the reconstruction method [13]. All the operations described below were implemented by means of Matlab ® software (The MathWorks Inc., Natick, MA, USA) and were systematically applied to all the recorded images.…”
Section: Mtv Image Post-processingmentioning
confidence: 99%
“…Subsequently, we have proposed a numerical method based on the advection-diffusion equation that was able to correctly reconstruct the velocity profile from the displacement of the tagged line. In a first step, the reliability of the method was proven by applying it to direct simulation Monte Carlo (DSMC) numerical experiments [13]. Later on, the method was proven to be valid also in the case of physical MTV experiments in confined non-rarefied flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation